Optimizing Maternal and Fetal Antibody Exposure and Dosing Regimens During Pregnancy Using a Physiologically Based Pharmacokinetic Model - Kardouh, Miramar Sami; Dunlap, Tyler C; Zhong, Rui; Tiley, Jacqueline B; Cao, Yanguang (Clinical pharmacology and therapeutics, 2025)
Therapeutic antibodies are often prescribed off-label to pregnant patients to treat inflammatory, autoimmune, or malignant conditions. Despite their broad use, the extent of fetal exposure to such therapeutic antibodies and the risk to fetal development remain largely unknown. Given the ethical challenges to conduct randomized trials in pregnant patients, modeling and simulation approaches offer an opportunity to yield mechanistic insights using data from observational studies. In this study, a physiologically based pharmacokinetic (PBPK) modeling framework was developed to predict maternal and fetal therapeutic antibody exposures throughout pregnancy. The model incorporates expression data on the placental neonatal Fc receptor (FcRn), a receptor critical to transplacental IgG transfer. FcRn-mediated transplacental antibody transfer was described by three endosomal compartments: (1) maternal vascular endothelial cells; (2) syncytiotrophoblast cells; and (3) fetal vascular endothelial cells. The model was calibrated and validated using endogenous IgG concentrations and pharmacokinetic data from > 2,000 non-pregnant subjects, 167 pregnant women, and 268 infants. Overall, the minimal PBPK model adequately captured the observations, with predictions falling within a twofold range of maternal and fetal concentrations as follows: infliximab (54% and 50%), adalimumab (100% and 70%), ustekinumab (38% and 41%), vedolizumab (92% and 77%), and etanercept (75% and 33%). In addition, the PBPK framework supported the evaluation of infliximab and adalimumab dosing regimens that maintain maternal therapeutic levels while minimizing fetal exposure. This study provides a generalizable PBPK framework including FcRn ontogeny, implemented in a user-friendly tool, to predict transplacental transfer of many biologics and to support appropriate dosing regimens throughout pregnancy.